Implication between Geophysical Events and the Variation of Seasonal Signal Determined in GNSS Position Time Series - Nistor, Sorin; Suba, Norbert-Szabolcs; El-Mowafy, Ahmed; Apollo, Michal; Malkin, Zinovy; Nastase, Edurard; Kudrys, Jack; Maciuk, Kamil (MDPI AG, 2021)
The seasonal signal determined by the Global Navigation Satellite System (GNSS), which is captured in the coordinate time series, exhibits annual and semi-annual periods. This signal is frequently modelled by two periodic signals with constant amplitude and phase-lag. The purpose of this study is to explore the implication of different types of geophysical events on the seasonal signal in three stages—in the time span that contains the geophysical events, before and after the geophysical event, but also the stationarity phenomena, which is analysed on approximately 200 reference stations from the EPN network since 1995. The novelty of the article is demonstrated by correlating three different types of geophysical events, such as earthquakes with a magnitude greater than 6-deg on the Richter scale, landslides, and volcanic activity, and analysing the variation in amplitude of the seasonal signal. The geophysical events situated within a radius of 30 km from the epicentre showed a higher seasonal value than when the timespan did not contain a geophysical event. The presence of flicker and random walk noise was computed using overlapping Hadamard variance (OHVAR) and the non-stationary behaviour of the time series of the CORS coordinates in the time-frequency analysis was done using continuous wavelet transform (CWT).